Analysis of the influence of visionary leadership, career development, and intellectual intelligence on employee performance at PT BCA, TBK, KCP Asia Medan - Angela Merlin; Sahat Simbolon; Nikous Soter Sihombing; Manda Dwipayani Bhastary (Enrichment : Journal of Management, 2025)
This study aims to determine the influence of visionary leadership, career development, and intellectual intelligence on employee performance at PT Bank Central Asia, Tbk, KCP Asia Medan from June 2025 to August 2025. The research employs a descriptive and quantitative method. The research subjects are the employees of PT Bank Central Asia, Tbk, KCP Asia Medan, with a population of 91 employees. The instrument used is a questionnaire to collect data on the variables of visionary leadership, career development, intellectual intelligence, and employee performance. The data analysis method included are: validity test, reliability test, descriptive analysis, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, simultaneous coefficient test (F-test), and coefficient of determination test. The results of the descriptive analysis show that the variables of visionary leadership and intellectual intelligence fall into the very good category, while the variables of career development and employee performance fall into the good category at PT Bank Central Asia, Tbk, KCP Asia Medan. Based on the results of the partial hypothesis test or t-test, the variables of visionary leadership, career development, and intellectual intelligence have a positive and significant influence on employee performance at PT Bank Central Asia, Tbk, KCP Asia Medan. Simultaneously, visionary leadership, career development, and intellectual intelligence also have a positive and significant effect on employee performance at PT Bank Central Asia, Tbk, KCP Asia Medan. The contribution of the variables of visionary leadership, career development, and intellectual intelligence to employee performance is 0.611 or 61.10%, while the remaining 38.90% is influenced by other factors outside this study, such as job stress, work discipline, and others.